Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To determine the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex] that satisfy the equation
[tex]\[ x^2 - 4x + 9 = (x + a)^2 + b \][/tex]
we will follow a step-by-step approach to equate coefficients from both sides of the equation.
### Step 1: Expand the Right-hand Side
First, expand [tex]\((x + a)^2 + b\)[/tex]:
[tex]\[ (x + a)^2 + b = (x^2 + 2ax + a^2) + b \][/tex]
So the right-hand side becomes:
[tex]\[ x^2 + 2ax + a^2 + b \][/tex]
### Step 2: Equate the Given Equation with the Expanded Right-hand Side
Rewrite the given equation by equating it with our expanded expression:
[tex]\[ x^2 - 4x + 9 = x^2 + 2ax + a^2 + b \][/tex]
### Step 3: Compare Coefficients of Corresponding Powers of [tex]\(x\)[/tex]
Let's compare the coefficients of like terms from both sides of the equation.
1. Coefficient of [tex]\(x^2\)[/tex]:
[tex]\[ 1 = 1 \][/tex]
2. Coefficient of [tex]\(x\)[/tex]:
[tex]\[ -4 = 2a \][/tex]
Solving for [tex]\(a\)[/tex]:
[tex]\[ 2a = -4 \implies a = -2 \][/tex]
3. Constant term:
[tex]\[ 9 = a^2 + b \][/tex]
Substitute [tex]\(a = -2\)[/tex] into this equation:
[tex]\[ 9 = (-2)^2 + b \][/tex]
Simplify and solve for [tex]\(b\)[/tex]:
[tex]\[ 9 = 4 + b \implies b = 9 - 4 \implies b = 5 \][/tex]
### Step 4: State the Solution
The values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex] that satisfy the equation are:
[tex]\[ a = -2 \quad \text{and} \quad b = 5 \][/tex]
[tex]\[ x^2 - 4x + 9 = (x + a)^2 + b \][/tex]
we will follow a step-by-step approach to equate coefficients from both sides of the equation.
### Step 1: Expand the Right-hand Side
First, expand [tex]\((x + a)^2 + b\)[/tex]:
[tex]\[ (x + a)^2 + b = (x^2 + 2ax + a^2) + b \][/tex]
So the right-hand side becomes:
[tex]\[ x^2 + 2ax + a^2 + b \][/tex]
### Step 2: Equate the Given Equation with the Expanded Right-hand Side
Rewrite the given equation by equating it with our expanded expression:
[tex]\[ x^2 - 4x + 9 = x^2 + 2ax + a^2 + b \][/tex]
### Step 3: Compare Coefficients of Corresponding Powers of [tex]\(x\)[/tex]
Let's compare the coefficients of like terms from both sides of the equation.
1. Coefficient of [tex]\(x^2\)[/tex]:
[tex]\[ 1 = 1 \][/tex]
2. Coefficient of [tex]\(x\)[/tex]:
[tex]\[ -4 = 2a \][/tex]
Solving for [tex]\(a\)[/tex]:
[tex]\[ 2a = -4 \implies a = -2 \][/tex]
3. Constant term:
[tex]\[ 9 = a^2 + b \][/tex]
Substitute [tex]\(a = -2\)[/tex] into this equation:
[tex]\[ 9 = (-2)^2 + b \][/tex]
Simplify and solve for [tex]\(b\)[/tex]:
[tex]\[ 9 = 4 + b \implies b = 9 - 4 \implies b = 5 \][/tex]
### Step 4: State the Solution
The values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex] that satisfy the equation are:
[tex]\[ a = -2 \quad \text{and} \quad b = 5 \][/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.